Research & Development Review of Open-pit Mine Autonomous Haulage Operation System - LU Xiangyang; CAI Jianye; LAN Deshao; YIN Chao (Kongzhi Yu Xinxi Jishu)
This paper summarizes the most recent development and progress of the open-pit mine autonomous haulage operation system in abroad and the development from scratch in domestic, and gives a brief introduction of the standardization work in the industry sector. On this basis, the key technical issues or the key requirements of open-pit mine autonomous haulage operation system is comprehensively described at systematical level,including nine core technical issues such as environment awareness and path planning,and five related technical issues such as line reconstruction and roadside monitoring. The system structure that satisfies the requirements is presented, consisting of ground management and supervision system, vehicle automation package onboard automated dumper, auxiliary operation package onboard collaborative machinery, data communication system and road side system. Eleven further research aspects including enhancement of automation grade, more comprehensive scenario description of event detection and response, as well as optimization of operation plan and regulation are proposed. The future of open-pit mine autonomous haulage operation system is prospected finally.